2020
DOI: 10.1017/s0950268820000965
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of the ‘bud event of norovirus-associated gastroenteritis’ in schools: does it work in the prevention of norovirus infection outbreaks in Shanghai?

Abstract: Outbreaks of norovirus-associated gastroenteritis have been reported in schools in recent decades in China. For early warning and response to infectious disease outbreaks, the Shanghai Infectious Diseases Bud Event Surveillance System (IDBESS) was established in 2016. Bud event is a term used for the early sign of a potential infectious disease outbreak in public settings when the first few cases appear. This study aimed to describe the epidemiological characteristics of Norovirus-associated gastroenteritis bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…The mean number of people affected in each outbreak (34 people per outbreak) is in line with the results found by Lian et al in a study conducted between 2014 and 2017 in China (mean of 34 people per outbreak) ( 27 ) and is not very different from that described by Wikswo et al in outbreaks of person-to-person transmission in the US in 2009–2010 (mean of 44 people per outbreak) ( 24 ) or from the mean of 40 people per outbreak observed by the same authors in 2009–2013 ( 28 ). He et al found a median of 16 persons affected by outbreaks (range 5 to 148) in Shanghai schoolchildren between June 2016 and December 2017 ( 11 ).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…The mean number of people affected in each outbreak (34 people per outbreak) is in line with the results found by Lian et al in a study conducted between 2014 and 2017 in China (mean of 34 people per outbreak) ( 27 ) and is not very different from that described by Wikswo et al in outbreaks of person-to-person transmission in the US in 2009–2010 (mean of 44 people per outbreak) ( 24 ) or from the mean of 40 people per outbreak observed by the same authors in 2009–2013 ( 28 ). He et al found a median of 16 persons affected by outbreaks (range 5 to 148) in Shanghai schoolchildren between June 2016 and December 2017 ( 11 ).…”
Section: Discussionsupporting
confidence: 64%
“…Lian et al in China between 2014 and 2017 found that 47.98% of affected schoolchildren were in primary school versus 16.86% in early childhood education ( 27 ). Wang et al found that 54.9% of affected children in Shanghai in 2017 were primary school children compared with 39.73% in early childhood education ( 25 ) and He et al in Shanghai between June 2016 and December 2017 found that 61.08% of affected children were in primary school ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there is the norovirus, which is a well-known infectious gastrointestinal disease. It is so severe in Chinese schools that in 2016 the Shanghai government implemented a detection system to warn of pervasive virus infection [5]. Sadly, no specific treatment has yet been discovered [6].…”
Section: Infectious Gastrointestinal Diseasesmentioning
confidence: 99%